Alternative Response Criteria (Choi, European Association for the Study of the Liver, and Modified Response Evaluation Criteria in Solid Tumors [RECIST]) Versus RECIST 1.1 in Patients With Advanced Hepatocellular Carcinoma Treated With Sorafenib. (20th March 2014) - Ronot, Maxime; Bouattour, Mohamed; Wassermann, Johanna; Bruno, Onorina; Dreyer, Chantal; Larroque, Béatrice; Castera, Laurent; Vilgrain, Valérie; Belghiti, Jacques; Raymond, Eric; Faivre, Sandrine
Abstract : Introduction: Response Evaluation Criteria in Solid Tumors, version 1.1 (RECIST 1.1), may underestimate activity and does not predict survival in patients with hepatocellular carcinoma (HCC) treated with sorafenib. This study assessed the value of alternative radiological criteria to evaluate response in HCC patients treated with sorafenib. Patients and Methods: A retrospective blinded central analysis was performed of computed tomography (CT) scans from baseline and the first tumor evaluation in consecutive patients treated with sorafenib over a 2‐year period in a single institution. Four different evaluation criteria were used: Choi, European Association for the Study of the Liver (EASL), modified RECIST (mRECIST), and RECIST 1.1. Results: Among 82 HCC patients, 64 with Barcelona Clinic Liver Cancer stage B‐C were evaluable with a median follow‐up of 22 months. Median duration of sorafenib treatment was 5.7 months, and median overall survival was 12.8 months. At the time of the first CT scan, performed after a median of 2.1 months, Choi, EASL, mRECIST, and RECIST 1.1 identified 51%, 28%, 28%, and 3% objective responses, respectively. Responders by all criteria showed consistent overall survival >20 months. Among patients with stable disease according to RECIST 1.1, those identified as responders by Choi had significantly better overall survival than Choi nonresponders (22.4 vs. 10.6 months; hazard ratio: 0.43, 95% confidence interval: 0.15–0.86, p = .0097). Conclusion: Choi, EASL, and mRECIST criteria appear more appropriate than RECIST 1.1 to identify responders with long survival among advanced HCC patients benefiting from sorafenib. Abstract : This study compared four radiological criteria used to evaluate long‐term survival in hepatocellular carcinoma patients treated with sorafenib. The results indicated that Choi criteria, European Association for the Study of the Liver, and modified Response Evaluation Criteria in Solid Tumors were more appropriate methods than Response Evaluation Criteria in Solid Tumors, version 1.1, for identifying patients with long‐term survival. Abstract : 摘要 简介 实体瘤疗效评价标准 1.1 版（RECIST 1.1）可能低估了接受索拉非尼治疗的肝细胞癌（HCC）患者中的活性，且对生存期未作预测。这项研究评估了替代放射学标准的价值，以便评价索拉非尼治疗对 HCC 患者的疗效。 患者与方法 对 2 年内在单个机构接受索拉非尼连续治疗患者的基线和首次肿瘤评估的计算机断层扫描（CT）结果进行了一项回溯性、盲态、集中分析。采用了四种不同的评价标准： Choi、欧洲肝脏研究学会（EASL)、改良的 RECIST（mRECIST）以及 RECIST 1.1。 结果 在 82 名 HCC 患者中，64 名巴塞罗那临床肝癌 B‐C 期患者可作评价，中位随访期为 22 个月。索拉非尼治疗的中位持续时间为 5.7 个月，中位整体生存期为 12.8 个月。在中位时间 2.1 个月之后进行首次 CT 扫描时，Choi、EASL、mRECIST 和 RECIST 1.1 所确定的客观见效率分别为 51%、28%、28% 和 3%。所有标准都显示见效者的整体生存期均 >20 个月。在按 RECIST 1.1 标准界定为病情稳定的患者中，根据 Choi 确定为见效者之患者的整体生存期显著好于 Choi 非见效者（22.4 相比 10.6 个月；风险比：0.43，95% 置信区间： 0.15–0.86，p = .0097）。 结论 Choi、EASL 和 mRECIST 标准似乎比 RECIST 1.1 更适合确定受益于索拉非尼的晚期 HCC 患者中生存期长的见效者。 The Oncologist 2014;19:394–402